VISUALIZATION OF THE PROCESS OF TEMPERATURE CONTROL IN THE GREENHOUSE WITH THE HELP OF CODESYS COMPLEX PROGRAM - Safarov I. U (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article focuses on the possibilities of using modern innovative technologies in production processes, including the complex programming environment CodeSys. It provides information on the tasks of visualization in the separate (autonomous) use of heating and ventilation systems using the complex programming environment CodeSys from modern technologies for automation of greenhouses. This article describes the implementation of technological processes in the form of animation with the help of visualization tools.